2023
DOI: 10.1049/rpg2.12773
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated active and reactive power management for enhancing PV hosting capacity in distribution networks

Rezvaneh Golnazari,
Saeed Hasanzadeh,
Ehsan Heydarian‐Forushani
et al.

Abstract: This paper proposes an operational planning model based on optimal active and reactive power control strategies to enhance solar photovoltaics (PV)’ hosting capacity in distribution networks. Reactive power control is carried out through optimum static VAr compensators (SVCs) placement, while active power control is performed through flexible loads, particularly shiftable and interruptible loads. The first stage of the proposed two‐stage stochastic model assigns decision‐making regarding calculating PV hosting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…These approaches can be combined with other HC enhancement techniques to increase the merits however they require more attention to avoid their drawbacks on other systems parameters that may be performed maloperation of protection devices [360]- [362]. In [334], [363], [364], the ANM approaches are applied for coordinate control and planning of various components, such as ESSs, OLTC, and EVs, based on the ADNs with integrated DERs under their uncertainties. While in [365]- [367], factacting devices like PV inverters, and EV aggregators, are used to perform coordinated control for minimizing energy loss and sustaining optimal operation.…”
Section: E Advanced Network Management Approachesmentioning
confidence: 99%
“…These approaches can be combined with other HC enhancement techniques to increase the merits however they require more attention to avoid their drawbacks on other systems parameters that may be performed maloperation of protection devices [360]- [362]. In [334], [363], [364], the ANM approaches are applied for coordinate control and planning of various components, such as ESSs, OLTC, and EVs, based on the ADNs with integrated DERs under their uncertainties. While in [365]- [367], factacting devices like PV inverters, and EV aggregators, are used to perform coordinated control for minimizing energy loss and sustaining optimal operation.…”
Section: E Advanced Network Management Approachesmentioning
confidence: 99%
“…On the other hand, several studies have focused on active and reactive power management to enhance DER hosting capacity in distribution networks [25]. Research has shown that utilizing reactive power control positively impacts the enhancement of DER hosting capacity while reducing power flow constraint violations.…”
Section: Introductionmentioning
confidence: 99%